In vitro evaluation of antimicrobial features of sugammadex - Volkan Hanci; Ahmet Vural; Sevgi Yılmaz Hanci; Hasan Ali Kiraz; Dilek Ömür; Ahmet Ünver (Brazilian Journal of Anesthesiology, 2014)
Background: Drugs administered by intravenous routes may be contaminated during several stages of production or preparation. Sugammadex is a modified gamma cyclodextrin. While research into the antibacterial effects of varieties of cyclodextrin is available, there are no studies focusing on the antibacterial effects of sugammadex. This study investigates the in vitro antimicrobial activity of sugammadex. Materials and methods: The in vitro antimicrobial activity of sugammadex was investigated using the broth microdilution method. The pH of the test solution was determined using a pH meter. The test microorganisms included Staphylococcus aureus ATCC 29213, Enterococcus fecalis ATCC 29212, Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853. In the second phase of the study 100 mg/mL sugammadex (50 μg) was contaminated with test microorganisms (50 μg), including S. aureus ATCC 29213, E. fecalis ATCC 29212, E. coli ATCC 25922 and P. aeruginosa ATCC 27853, left to incubate for 24 h and then the bacterial production in sugammadex was evaluated. Results: The pH of the test solutions ranged between 7.25 and 6.97. Using the microdilution method, sugammadex had no antibacterial effect on S. aureus, E. fecalis, E. coli and P. aeruginosa at any concentration. In the second phase of the study bacterial production was observed after 24 h in 100 mg/mL sugammadex contaminated with the test microorganisms S. aureus, E. fecalis, E. coli and P. aeruginosa. Conclusions: Sugammadex had no antimicrobial effect on the test microorganisms, S. aureus, E. fecalis, E. coli and P. aeruginosa. Care should be taken that sterile conditions are maintained in the preparation of sugammadex; that the same sugammadex preparation not be used for more than one patient; and that storage conditions are adhered to after sugammadex is put into the injector. Keywords: Sugammadex, Antimicrobial effect, S. aureus, E. fecalis, E. coli, P. aeruginosa